TERAPI ISTIGHFAR SEBAGAI SOLUSI UNTUK MENCEGAH BULLYING DIKALANGAN PELAJAR - Arifin, Imamul; Nadia Putri, Salsabila; Aini Apriliyanti, Nurul (Jurnal Psikologi Islam, 2021)
ABSTRACT This research is based on the rampant cases of bullying among students in Indonesia whose actions can occur anywhere, especially places that are not supervised by teachers or other adults. Research data from the Program for International Students Assessment (PISA) 2018 shows that 41.1% of students who admit to having experienced bullying in Indonesia. The student number of victims of bullying is far above the average for OECD member countries, which is only 22.7%. In addition, Indonesia is in the fifth highest position out of 78 countries as the country with the most students experiencing bullying, which causes psychological problems for the victim (the victim is called a bully boy or bully girl) in the form of stress (which appears in the form of physical or psychological disorders, or both. ; for example, difficulty eating, physical pain, fear, low self-esteem, depression, anxiety, etc.) This study aims to analyze the level of bullying in Indonesia and the correlation of the effects of istigfar therapy inspired by QS. Al-Baqarah: 199. The method used in this research is literature study with descriptive qualitative analysis method. Keywords: Psychology, Bullying, Istighfar Therapy. ABSTRAK Penelitian ini didasari oleh maraknya kasus pembullyan dikalangan pelajar di Indonesia yang tindakannya bisa terjadi dimana saja, terutama tempat-tempat yang tidak diawasi oleh guru atau orang dewasa lainnya. Data hasil riset Programme for International Students Assessment (PISA) 2018 menunjukkan murid yang mengaku pernah mengalami perundungan (bullying) di Indonesia sebanyak 41,1%. Angka murid korban bully ini jauh di atas rata-rata negara anggota OECD yang hanya sebesar 22,7%. Selain itu, Indonesia berada di posisi kelima tertinggi dari 78 negara sebagai negara yang paling banyak murid mengalami perundungan, yang menimbulkan gangguan psikis bagi korbannya (korban disebut bully boy atau bully girl) berupa stress (yang muncul dalam bentuk gangguan fisik atau psikis, atau keduanya; misalnya susah makan, sakit fisik, ketakutan, rendah diri, depresi, cemas, dan lainnya).Penelitian ini bertujuan untuk menganalisis tingkat pembulliyan di Indonesia serta korelasi dari efek terapi istigfar yang terispirasi dari Q.S. Al- Baqarah: 199. Metode yang digunakan dalam penelitian ini yakni studi literatur dengan metode analisis kualtatif deskriptif. Keywords: Psikologi, Bullying, Terapi Istighfar.